Microscopia de campo próximo aplicada ao estudo dos domínios ferroelásticos - Dantas, Saulo Maia (2011)
A significant part of the nowadays scientific research is based on the synthesis, characterization and application of the nanostructured materials. In order to make possible a further understanding of the intriguing properties of these materials, many techniques with nanometric and even subnanometric resolution have been created during the last 50 years and are passing through a process of continuous improvement. In spite of the great scientific and technical development on the available instrumentation, the optical characterization with nanometric resolution of these materials remains a challenge for researchers from all over the world. In this context, techniques based on near field radiation have emerged as a great alternative for the diffraction limit break which is a nature imposed limit for conventional optical instruments. Besides this, contact near field microscopy in illumination mode acquires optical and topographical information of the material simultaneously. This capability permits the distinction between the real and topographic induced nanometric optical features. The domain phenomenon in crystals has been a subject of interest for crystallographers since crystallography started to develop as a scientific branch. The obvious reasons are the beauty of some domain patterns as well as evident and challenging symmetry relations between their constituents. The ferroelastic domains are one of the important kinds of domains presented by crystals. They have, sometimes, very small dimensions without inducing any topographic element on the sample. On the other side the optical behavior of different domains under almost the same measurement condition may be very dissimilar. Such characteristics make then an ideal class of materials for contact near field microscopy in illumination mode based studies. Ferroelastic domains images, using near-field optical microscopy in illumination and contact mode, were obtained with a nanometric resolution. Such images, in general, presented very little relation with the topographical structure of the material, revealing optical and structural features such as occurrence of the waveguide effect in the domains, domain´s dimensions and presence of dislocations on the crystalline structure.